Prediction of adverse outcomes in the long-term follow-up period in patients with chronic heart failure who have suffered a myocardial infarction - Yurii А. Trusov; Yurii V. Shchukin; Larisa V. Limareva (Наука и инновации в медицине)
Aim – to determine the prognostic significance of global longitudinal strain of the left ventricle (GLS) and soluble stimulating growth factor (sST2) in patients with chronic heart failure (CHF) after myocardial infarction (MI) in the annual follow-up period.